IMMEDIATE AND LONGTERM RESULTS OF ENDOVASCULAR STENT-GRAFTING IN DISSECTIONS AND ATHEROSCLEROTIC ANEURYSMS OF THORACIC AORTA - Kyaw K. Latt; Alexey A. Moiseev; Natalya R. Chernaya; Konstantin N. Vasilyev; Nikolay L. Bayandin; Viktor A. Stupin («REMEDIUM GROUP» Ltd., 2018)
Objective: to analyze the results of endovascular stent-graftingin dissections and atherosclerotic aneurysms of descending part of thoracic aorta.Material and method: in this analysis includes 28 patients with dissections and atherosclerotic aneurysms of descending part of thoracic aorta. Acute aortic dissection type 3 was occurred in 10 patients and two of them were complicated with rupture into the left pleural cavity. 10 patients with chronic aortic dissection type bunderwent operations and one of them was complicated with rupture into the left pleural cavity. Among 8 operated patients due to chronic aneurysms of descending part of thoracic aorta, 4 patients were manifested with symptoms of hemothorax. In 3 patients with aortic dissection type 1 in long-term period, endovascular stent-grafting was performed concerning with the dilatation of descending thoracic aorta and patent false lumen. During in-hospital and long-term periods immediate clinical results, serious clinical complications and long-term survival were compared.Results: technical success of endovascular stent-grafting was achieved in 100 % of cases. In-hospital mortality was 4 (14,2 %) and 30-day mortality was 3 (10,7 %). Events of paraplegia, TIA (Transient Ischemic Attack), prosthetic infection were not found in our research. Two clinical occurrences of vascular approach site complication were found; one case of endoleak type 1 and stent-graft dislocation which required repeated endovascular stent-grafting and one case of endoleak type 2 which was performed subclaviancarotid bypass and ligation of left subclavian artery. Prolong intubation was needed in 5 patients (18,5 %).conclusion: Endovascular stent-grafting in dissections and atherosclerotic aneurysms of descending part of thoracic aorta contributes good immediate clinical results associating with less quantity of serious complications.